Breaking the taboo of using the nursing process: lived experiences of nursing students and faculty members - Amir Shahzeydi; Parvaneh Abazari; Fatemeh Gorji-varnosfaderani; Elaheh Ashouri; Shahla Abolhassani; Fakhri Sabohi (BMC, 2024)
Abstract Background Despite the numerous advantages of the nursing process, nursing students often struggle with utilizing this model. Therefore, studies suggest innovative teaching methods to address this issue. Teaching based on real clinical cases is considered a collaborative learning method that enhances students' active learning for the development of critical thinking and problem-solving skills. In this method, students can acquire sufficient knowledge about patient care by accessing authentic information. Objective The aim of the present study was to investigate the experiences of nursing students and faculty members regarding the implementation of nursing process educational workshops, based on real case studies. Design A qualitative descriptive study. Participants 9 Nursing students and 7 faculty members from the Isfahan School of Nursing and Midwifery who attended the workshops. Methods This qualitative descriptive study was conducted from 2021 to 2023. Data was collected through semi-structured individual and focus group interviews using a qualitative content analysis approach for data analysis. Results After analyzing the data, a theme titled "Breaking Taboos in the Nursing Process" was identified. This theme consists of four categories: "Strengthening the Cognitive Infrastructure for Accepting the Nursing Process," "Enhancing the Applicability of the Nursing Process," "Assisting in Positive Professional Identity," and "Facilitating a Self-Directed Learning Platform." Additionally, thirteen subcategories were obtained. Conclusion The data obtained from the present study showed that conducting nursing process educational workshops, where real clinical cases are discussed, analyzed, and criticized, increases critical thinking, learning motivation, and understanding of the necessity and importance of implementing the nursing process. Therefore, it is recommended that instructors utilize this innovative and effective teaching method for instructing the nursing process.